A comparative In vivo efficacy of three spiral techniques versus incremental technique in obturating primary teeth - Shalini Chandrasekhar; Madu Ghanashyam Prasad; Ambati Naga Radhakrishna; Kaniti Saujanya; N V K Raviteja; B Deepthi; J Ramakrishna (Wolters Kluwer Medknow Publications, 2018)
Background: The aim of this study was to evaluate the efficiency of four different obturating techniques in filling the radicular space in primary teeth. Materials and Methods: This clinical trial was carried out on 34 healthy, cooperative children (5-9 years) who had 63 carious primary teeth indicated for pulpectomy. They were divided into four groups, such that in each group, a total of 40 canals were allotted for obturation with respective technique. The root canals of selected primary teeth were filled with Endoflas obturating material using either bi-directional spiral (Group 1); incremental technique (Group 2), past inject (Group 3) or lentulo spiral (Group 4) according to the groups assigned. The effectiveness of the obturation techniques was assessed using postoperative radiographs. The assessment was made for a depth of fill in the canal, the presence of any voids using Modified Coll and Sadrian criteria. The obtained data were analyzed by using ANOVA test and unpaired t-test. Results: Bi-directional spiral and lentulo spiral were superior to other techniques in providing optimally filled canals (P< 0.05). The bi-directional spiral was superior to lentulo spiral in preventing overfill (P< 0.05). Conclusion: Based on the present study results, bi-directional spiral can be recommended as an alternate obturating technique in primary teeth.